Students' Views on the Utilization of the TikTok Application to Enhance Their Vocabulary - Pratiwi, Imas; Syafrizal, Syafrizal (Pencerah, 2024)
The objective of this study is to ascertain the students' perspectives regarding the utilization of the TikTok application for vocabulary acquisition. In particular, there are two research objectives: 1) To ascertain the students' perspectives regarding the utilization of the TikTok application for vocabulary acquisition; 2) To ascertain the benefits and drawbacks of utilizing the TikTok application to learn English. Descriptive qualitative methodology was implemented in this investigation. The students in class X at SMK Yuppentek 2 Tangerang participated in this study. This investigation implemented an open-ended questionnaire for data acquisition. Two conclusions are drawn from these results. Initially, students' perspectives regarding the utilization of the TikTok application for vocabulary acquisition. The research findings indicate that students have favorable attitudes toward the utilization of the TikTok application for vocabulary acquisition. Students concur that the TikTok application is a valuable tool for the acquisition of vocabulary, as it provides a more engaging learning experience and prevents them from becoming readily fatigued. In the process of studying vocabulary, students will acquire a wealth of knowledge regarding English vocabulary. The application provides subtitles beneath the original narrative, which facilitates comprehension and comprehension of the vocabulary. From a student's perspective, the TikTok application offers several benefits: it is visually appealing, it includes sounds that facilitate the recall of new vocabulary, and it includes subtitles that provide students with a clear understanding of the meaning of the vocabulary. This application is user-friendly, and the videos can be viewed at any time and in any location.